PENGARUH KONSENTRASI GIBERELIN DAN LAMA PERENDAMAN TERHADAP PERKECAMBAHAN BIJI SIRSAK (Anonna muricata L.) - Silvia Polhaupessy; Hermalina Sinay (Program Studi Pendidikan Biologi FKIP Unpatti, 2014)
Background: The aim of this research was want to know the effect of GA concentration with soaking time towards seedling germination of soursop, and to know whichone of the treatment that can give a very highest quality and quantity of seedling germination of soursop. Method: This research started from Juny until July 2011. Factorial pattern of completely randomized block design (RAL) were used in this research, which consist of two factors. First factor where concentration of GA with four level i.e. A1= 5 PPM, A2 = 10 PPM, A3 = 15 PPM, and A4 = 20 PPM. While the second factor where soaking time which consist of three level i.e. L1= soaking for six hour, L2 = soaking for twelve hours, L3 = soaking for twenty-four hours. Each combination with three replicated. Data collected were analyzed used analysis of variance at the significant level of Î± 0,05 and 0,01. Result: Percentage obtained at the A3L2 treatment i.e. 100 %, plant high 16,12 cm, and root length 12,99 cm. It can be concluding that GA and soaking time treatment, can affected the seedling germination of soursop. Conclusion: Based on the results obtained it can be concluded that the use of GA concentration and different soaking time on seed soursop significant effect on percentage germination, high germination and seedling root length.